The Interaction Between Non-Coding RNAs and Calcium Binding Proteins - Ghafouri-Fard, Soudeh; Majidpoor, Jamal; Shoorei, Hamed; Hussen, Bashdar Mahmud; Hadayat Jamal, Hazha; Baniahmad, Aria; Taheri, Mohammad; Mokhtari, Majid (Frontiers in Oncology, 2022)
Calcium binding proteins (CBP) are a group of proteins mediating the effects of calcium on cellular functions. These proteins can regulate calcium levels inside the cells and contribute in several cellular functions through transporting this ion across cell membranes or decoding related signals. Recent studies have shown that several non-coding RNAs interact with CBPs to affect their expression or activity. The interactions between these transcripts and CBPs have implications in the pathoetiology of human disorders, including both neoplastic and non-neoplastic conditions. In the current review, we describe the interactions between three classes of non-coding RNAs (long non-coding RNAs, circular RNAs, and microRNAs) and a number of CBPs, particularly CAB39, S100A1, S100A4, S100A7 and S100P. This kind of interaction has been verified in different pathological contexts such as drug-induced cardiotoxicity, osteoblasts cytotoxicity, acute lung injury, myocardial ischemia/reperfusion injury, proliferative diabetic retinopathy, glomerulonephritis, as well as a wide array of neoplastic conditions.